A New Scoring System for Prediction of Intravenous Immunoglobulin Resistance of Kawasaki Disease in Infants Under 1-Year Old - Wu, Shu; Long, Yuan; Chen, Selena; Huang, Yaqian; Liao, Ying; Sun, Yan; Zhang, Qingyou; Zhang, Chunyu; Yan, Hui; Qi, Jianguang; Liu, Xueqin; Chen, Yonghong; et al. (Frontiers in Pediatrics, 2019)
Background: Children with Kawasaki disease (KD) under 1-year old are at high risk for intravenous immunoglobulin (IVIG) resistance. The study was designed to explore the predictive measure of IVIG resistance in infants under 1-year old with KD. Methods: This study enrolled children under 1-year old suffering from KD in Peking University First Hospital and Wuhan Children's Hospital. All infants were divided into IVIG-responsive and IVIG-resistant groups. The differences in demographic characteristics, clinical features and laboratory examinations were compared and the risk factors of IVIG resistant KD were analyzed. Furthermore, a scoring system was developed for predicting IVIG resistance in KD infants and an external validation was performed. Result: A total of 282 infants (194 boys, median age of 7.0 months) were enrolled in this study, of whom 23 children were IVIG-resistant. Compared with IVIG-responsive infants, those in the IVIG-resistant group had a high neutrophil-to-lymphocyte ratio (NLR), high platelet-to-lymphocyte ratio (PLR), high mean platelet volume-to-lymphocyte ratio (MPVLR) in peripheral blood, and low serum albumin (ALB) and low serum sodium (Na) before IVIG therapy (all P < 0.01). Multiple regression analysis indicated that high levels of peripheral NLR and MPVLR, and low levels of serum ALB and Na were independent risk factors for IVIG resistant KD infants. A scoring system, which included peripheral NLR ≥ 2.69 (1 point), MPVLR ≥ 2.78 (1 point), serum albumin ≤ 30.7 g/L (1 point), and Na ≤ 135.2 mmol/L (1 point), was established. A cut-off value of a total score of 2 points or higher yielded a sensitivity of 87% and a specificity of 78.4%, with an area under the curve of 0.891. External validation with clinical diagnostic standard showed that a cut-off value of total score of 2 points or higher for predicting the IVIG-resistance yielded a sensitivity of 70.0% and a specificity of 75.1%. Conclusion: For the first time, we proposed a predictive model of IVIG resistance in KD infants under 1-year old. The scoring system, which accounts for baseline peripheral NLR, MPVLR, and serum albumin and sodium, predicts with relatively high sensitivity and specificity for IVIG-resistant infants with KD under 1-year old.